Petroleum Production Sharing Contracts in the Middle East: Application of Economic Evaluation and Decision-Making Modeling - Al Janahi, Ahmed; Kukreja, Gagan; Hamdan, Allam (International Journal of Energy Economics and Policy, 2019)
In this Study, the evolution and history of petroleum contracts is discussed with a focus on the recent major shift witnessed from Joint Operating Agreements (JOA) and Concession contracts to Production Sharing Agreements (PSA) due to the increase in the complexity of operations and funding difficulties especially from the government's side. In addition to that, the fiscal system of PSA's is studied as a legal instrument to allocate risk between the parties, identify ownership of assets, commitments and operational control. This study aims to figure out the application of economic evaluation for PSA's using Discounted Cash Flow Analysis (DCF) which is considered to be powerful in evaluating the investment performance by calculating Net Present Value (NPV) of cash flows and the Internal Rate of Return (IRR). The estimated production profile submitted in the PSA of interest was exaggerated. When a Monte-Carlo Simulation was run the riskier profile (P10) was the closest to the PSA production forecast. However, in such agreements usually the mid case scenario (P50) is taken into consideration. The NPV for the first 10 years in this project is around $0.45 Billion compared to the total NPV calculated using the economic model $1.26 Billion. However, the recent instability of the oil price in the last 10 years what causes this project in particular not to meet the target so far. The IRR calculated for the 10 years period is almost the hurdle rate 10% and this is again due to the unexpected NPV due to the oil price. To reduce the uncertainty, pilot projects needs to be conducted in the first year in smaller spacing to allow for the response to be detected faster and then develop a Field Development Plan (FDP). Keywords: Petroleum production sharing contracts; Economic evaluation; Decision-making modeling; Middle East. JEL Classifications: E23, K12, Q4 DOI: https://doi.org/10.32479/ijeep.7810